2015
DOI: 10.5296/ber.v5i1.6647
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Economic Growth in Nigeria: A Co-integration Analysis

Abstract: This paper establishes an empirical relationship between foreign direct investment (FDI) and economic growth in Nigeria under the framework of cointegration analysis over the period 1970-2010. The econometric evidence from the Engle Granger cointegration tests suggests that there is no long-run relationship between FDI and economic growth in Nigeria. However, there is a short-run dynamic relationship between FDI and economic growth. And finally the study concluded that, for the achievement of a long-run relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Trade openness as defined by the export plus import share of GDP though was not statistically significant at the 5% level but still has the potential to make growth inclusive. This is in agreement with Olatunji and Shahid (2015) when they revealed that the transfer of technology to less developed countries from developed nations lead to an increase in the productivity factor and that economic growth was facilitated by trade openness.…”
Section: Co-integration Resultssupporting
confidence: 89%
“…Trade openness as defined by the export plus import share of GDP though was not statistically significant at the 5% level but still has the potential to make growth inclusive. This is in agreement with Olatunji and Shahid (2015) when they revealed that the transfer of technology to less developed countries from developed nations lead to an increase in the productivity factor and that economic growth was facilitated by trade openness.…”
Section: Co-integration Resultssupporting
confidence: 89%
“…To begin with the trade and economic growth nexus, Ekpo (1995) obtained an inverse relationship between openness to trade and economic growth in Nigeria within a period of 23 years starting from 1970 to 1992. Oladipo (1998) while estimating the degree of relationship between openness to trade and growth in Nigeria 1982 1984 1986 1988 1990 1992 1994 1996 1998 2000 2002 2004 2006 2008 2010 2012 2014 2016 FDI AS % OF GDP applied quarterly data spanning from 1970 to 1996 with export to GDP ratio and trade to GDP ratio as proxies for trade openness. He obtained a positive correlation in the former but on the contrary, the later proxy produced a negative result.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The research (ibid) found that the effect is stronger for host countries with a higher level of institutional capability -as measured by the degree of property rights protection and bureaucratic efficiency in the host country. A more contemporary study by Olatunji and Shahid (2015), found a short-run dynamic relationship between FDI and economic growth, and suggested that the long-run relationship can be achieved through infrastructure development and political stability. However, extant literature also reveals that the main deterrents to attracting FDI in developing countries include: governance failure, problems of policy credibility, macroeconomic policy failures and poor liberalization policies (Anyanwu, 2011;Alfaro et al, 2004;Asiedu, 2003).…”
Section: Introductionmentioning
confidence: 99%